Self-assembled multilayers of polyethylenimine, DNA and gold nanoparticles. A study of electron transfer reaction - Ferreyra, Nancy Fabiana (2010)
The present manuscript describes studies of the electron transfer kinetics at gold electrodes modified by electrostatic self-assemblies of polyethylenimine (PEI), DNA and gold nanoparticles (NP) by Scanning Electrochemical Microscopy (SECM). Two redox mediators of similar structure, ferrocenemethanol (FcOH), and ferrocenecarboxylic acid (FcCOOH) were used to evaluate the effect of the electrode modification on the electron transfer process. For both redox probes, the observed electrochemical behavior was dependent of the charge of the external layer of the self-assembled structure. The corresponding apparent heterogeneous rate constant, k0, was determined. The effect of NP adsorption was also evaluated. Independently of the mediator used, an increase of the k0 was observed when NPs were incorporated, and the surfaces presented a conductive behavior similar to the bare gold electrode. SECM images using FcOH as redox mediator were also recorded. Variations in the normalized currents permitted to evaluate differences of the surface electroactivity due to the polymers and/or nanoparticles adsorption. © 2009 Elsevier B.V. All rights reserved.